BIOCHEMICAL METHOD OF RECEIVING THE ETHYL ALCOHOL - Гарасимчук, С. М.; Азаренкова, А. А.; Бойченко, М. С.; Барановський, М. Н. (Science-based technologies, 2014)
The article considers the main types of raw materials used for receiving the ethyl alcohol biochemical method. Analyzed technological process of production of ethyl alcohol biochemical method by fermentation of sugars under influence of enzymes of yeast. Provides an overview of the technological process of obtaining alcohol biochemical method that will help develop more effective ways to recycle and make alcohol production wasteless, environmentally and economically justified. Classification of biochemical method by types of raw materials used (grow sugar-containing (waste of sugar manufacture, beets, fruit, berries, grapes); starch- containing (potatoes, rye, oats, barley, corn, wheat); containing cellulose (wood, wood chips, straw, film cereals and other waste plants).